Genetic identification of burned corpses as a part of disaster victim identification effort. (December 2015) - Ricci, U.; Carboni, I.; Iozzi, S.; Nutini, A.L.; Contini, E.; Torricelli, F.; Focardi, M.; Pinchi, V.; Mari, F.; Norelli, ​G.A.
Abstract: Forensic genetics is extremely useful for the resolution of criminal cases, identification of missing persons and paternity/kinship testing. The Italian town of Prato, near Florence, has been a centre of Italian textile industry since the 12th century and now it hosts a number of Chinese-run textile factories producing garments for export across Europe. In December 2013 a fire burned a factory where eleven Chinese workers were employed. The fire was due to a short circuit and it surprises the workers in the makeshift dormitory. After the fire was extinguished, remains of seven people were found by rescuers. The identification was carried out in accordance with Interpol protocols (AM and PM form) and in every case one of the three primer identifiers was satisfied. Relatives of the victims were available for information and biological samples' collection. Here, we show the protocol adopted in the forensic genetics laboratory that included the use of a wide battery of markers STRs, Y-STR and biostatistics evaluation of different assumptions about the identification of these persons.